Flat and Spatial Curves - Jabborov, Anvar Egamovich; Mamurova, Feruza Islomovna (European Journal of Life Safety and Stability (2660-9630), 2022)
Polyhedra have beautiful shapes, for example, regular, semi-regular and star polyhedra. A regular polyhedron is a polyhedron whose all faces are regular equal polygons, and all dihedral angles are equal.